2014
DOI: 10.1542/peds.2013-3153
|View full text |Cite
|
Sign up to set email alerts
|

Activity Levels in Mothers and Their Preschool Children

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Physical activity is beneficial to health. Parents are crucial in shaping children' s behaviors, with active mothers appearing to have active children. Little is known about this association in preschool-aged children, or about factors influencing activity in mothers of young children. WHAT THIS STUDY ADDS:Mother-child physical activity levels were positively associated and influenced by temporal and demographic factors. Maternal activity levels were low, and influences differ by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
116
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(132 citation statements)
references
References 45 publications
14
116
1
1
Order By: Relevance
“…However, Hinkley et al 23 pointed out that children whose parents had an active lifestyle tended to be more active. Likewise, Hesketh et al 24 indicated that maternal daily PA levels were associated with every PA intensity levels in preschoolers.…”
Section: Discussionmentioning
confidence: 98%
“…However, Hinkley et al 23 pointed out that children whose parents had an active lifestyle tended to be more active. Likewise, Hesketh et al 24 indicated that maternal daily PA levels were associated with every PA intensity levels in preschoolers.…”
Section: Discussionmentioning
confidence: 98%
“…Sin embargo, Hinkley et al, 23 señalaron que los niños con padres activos tendían a ser más activos. Del mismo modo, Hesketh et al, 24 indicaron que los niveles de AF diaria de la madre se asociaban con todas las intensidades de AF de los niños preescolares.…”
Section: Discussionunclassified
“…413 Studies have also found the more inactive the mother, the more inactive the child, and the more physically active the mother, the more physically active the child early in life. 414 Mississippi had the highest reported percentage of inactivity among adults at 36.8 percent.…”
Section: Us Eating Habitsmentioning
confidence: 91%